2009
DOI: 10.21273/hortsci.19.3.660
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selected Fine-leaf Fescue Cultivars for Their Turfgrass Quality and Weed Suppressive Ability in Field Settings

Abstract: A series of field studies were conducted from 1999 to 2005 in Ithaca, NY, at the Cornell Turfgrass Research Center as part of the National Turfgrass Evaluation Program (NTEP) to evaluate a collection of 78 fine-leaf fescue cultivars (Festuca spp.) for turfgrass quality, seedling vigor, and ability to inhibit the establishment of common annual and perennial weeds. Using these criteria, we evaluated the overall suitability of the cultivars for use in turfgrass settings, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 13 publications
3
67
3
Order By: Relevance
“…In the case of a perennial sod such as that formed by fine leaf fescues, the potential exists for nearly continual production during the growing season and a localized release of root exudates within the rhizosphere to germinating weed seeds. Additionally, we have observed weed suppression by certain fine leaf fescues over multiple locations and years and have determined that this suppression is cultivar dependent (Bertin et al 2009). Further studies are now underway to directly assess m-tyrosine release rates and to evaluate toxicity within the rhizosphere of living fine fescue roots.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of a perennial sod such as that formed by fine leaf fescues, the potential exists for nearly continual production during the growing season and a localized release of root exudates within the rhizosphere to germinating weed seeds. Additionally, we have observed weed suppression by certain fine leaf fescues over multiple locations and years and have determined that this suppression is cultivar dependent (Bertin et al 2009). Further studies are now underway to directly assess m-tyrosine release rates and to evaluate toxicity within the rhizosphere of living fine fescue roots.…”
Section: Resultsmentioning
confidence: 98%
“…Establishment vigor has been shown to vary not only among the taxa but also among cultivars within a species or subspecies (Bertin, Senesac, Rossi, DiTommaso, & Weston, 2009; Kim, 2013). Meyer and Funk (1989) reported strong creeping red fescue to have the advantage in establishment vigor over Chewings fescue.…”
Section: Establishmentmentioning
confidence: 99%
“…Selecting a turfgrass cultivar that can suppress weed development would be beneficial for turfgrass breeding. It was reported that chewing's fescue and strong creeping fescue were strongly weed suppressive [192]. Interestingly, even to the same disease, the pathogens are different.…”
Section: Biotic Stressmentioning
confidence: 99%